(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize current evidence on the effectiveness of High-Flow Nasal Cannula (HFNC) oxygen therapy in the management of respiratory failure caused by bronchiolitis in children. Methods: This review analyzed 55 studies evaluating the clinical outcomes of HFNC therapy in children under two years of age with bronchiolitis-associated respiratory failure. Data were retrieved from online databases up to June 30, 2025. Results: Most studies on HFNC in bronchiolitis were observational (69.1%), focusing on children under 24 months (96.4%) with moderate to severe disease (70.9%), and were primarily conducted in pediatric intensive care units (38.2%). However, inconsistency in failure definitions and lack of standardized treatment protocols limited cross-study comparability. Overall, HFNC demonstrated high efficacy and safety, with approximately 70% of studies reporting a success rate ≥70%, a very low mortality rate (0.2%; 19/24 studies reported no deaths), and rare serious complications (<1.5%). HFNC significantly improved respiratory rate, heart rate, and clinical scores, showing superiority over standard oxygen therapy (SOT) and better tolerance compared to nasal continuous positive airway pressure (nCPAP) or noninvasive ventilation (NIV). Conclusion: HFNC is a safe and effective therapy for bronchiolitis in children. However, current literature lacks standardization regarding initiation criteria, flow settings, and definitions of treatment failure or high-risk cases.